TEACHING STUDENTS TO THINK CRITICALLY IN READING LITERACY LESSONS - Parpiyev Odil Olimovich (Modern American Journals, 2025)
This article discusses pedagogical methods and methodological approaches to developing students' critical thinking skills through text analysis in reading literacy classes. Pedagogical methods for developing students' logical thinking and independent assessment of situations presented in the text through in-depth text analysis are considered. The theoretical ideas presented earlier are substantiated by providing evidence.
Keywords: 4K model, critical thinking, reading literacy, text analysis, critical thinking, method.